P252 Once-daily NVA237 improves symptoms, and reduces COPD exacerbations and associated hospitalisations: the GLOW1 trial. (2nd December 2011) - D'Urzo, A; van Noord, J A; Martin, C; Horton, R; Banerji, D; Lu, Y; Alagappan, V K T; Overend, T
Abstract : Introduction: Symptoms profoundly impact daily life of COPD patients. We assessed the influence of the once-daily (qd) long-acting muscarinic antagonist (LAMA) NVA237 (glycopyrronium bromide) on symptoms and exacerbations in patients with moderate-to-severe COPD. Methods: Patients were randomised (2:1) to 26 weeks double-blind treatment with NVA237 50 μg qd or placebo (PBO) via a single-dose dry powder inhaler (Breezhaler ® device). Efficacy was assessed by bronchodilation (trough FEV1 at Week 12), breathlessness on the transition dyspnoea index (TDI), HRQoL via the St. George's Respiratory Questionnaire (SGRQ), and rescue medication use. The effect on COPD exacerbations and related hospitalisations was also assessed. Results: 822 patients were randomised; 80.5% completed. NVA237 significantly increased total TDI focal score vs PBO at Week 26 (difference 1.04, 95% CI 0.583 to 1.504; p<0.0001); exceeding the minimum clinically important difference ([MCID] =1 point). Significantly more patients achieved MCID in TDI score with NVA237 (61.3% vs 48.3%; OR 1.74, 95% CI 1.249 to 2.415; p=0.001). SGRQ total score was significantly reduced with NVA237 (−2.81; p=0.004); % of patients achieving a clinically meaningful improvement in SGRQ (=4 point reduction) was significantly higher with NVA237 (56.8% vs 46.3%; OR 1.58, 95% CI 1.138 to 2.196; p=0.006). NVA237 significantly reduced rescue medication use at Week 26 (−0.46 puffs/day, p=0.005). NVA237 significantly prolonged time to first moderate/severe COPD exacerbation by 31% (HR 0.69, 95% CI 0.50 to 0.949; p=0.023) and time to first severe COPD exacerbation necessitating hospitalisation (HR 0.35, 95% CI 0.141 to 0.857; p=0.022). NVA237 significantly reduced hospitalisations due to COPD exacerbation (OR 0.34; p=0.024). Conclusion: Once-daily NVA237 provided significant improvements in dyspnoea and SGRQ total score, with lower rescue medication use, and reduced risk of exacerbation and associated hospitalisations vs PBO.